Equilibrium Selection and Monetary Policy; A Natural Rate Perspective - Alexander Meyer-Gohde (Verein für Socialpolitik, 2010)
The analysis of this paper examines the uniqueness of equilibria in a broad class of dynamic monetary models that satisfy Lucas's (1972) natural rate hypothesis (NRH). For a given demand specification, the resulting bounds for determinacy on monetary policy's interest rate rule are the same for all supply specifications, save isolated singularities. Thus, the monetary authority needs no knowledge of the supply side to ensure determinacy - with the standard dynamic IS-equation, determinacy is solely a function of parameters in the interest rate. Cochrane's (2007) criticism of determinacy as a means of ascertaining equilibrium in monetary models is confronted with this broad class appended to include money. With monetary policy specified only by the nominal interest rate, the critique is verified with hyperinflations and -deflations being accommodated by monetary policy. A credible commitment on behalf of the monetary authority to keep the money growth rate finite suffices to rule out the accommodated nominal explosions.
Keywords: E52; E58; C62; 330; Indeterminacy; Taylor rule; Learning; Sticky prices; Natural rate hypothesis